Turnaround management and blue oceans strategy implementation (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
This paper aims to give the main guidelines for strategic implementation of blue oceans strategy and how this kind of strategy is a part of turnaround management. Also, the author strives to underline the importance of Management Control Systems(MCSs) in this strategy implementation process. The author also briefly examines the importance of cultural expressions inside the company in terms of strategy implementation.